Carbon‐Coated Hierarchical SnO2 Hollow Spheres for Lithium Ion Batteries. Issue 17 (16th March 2016) - Liu, Qiannan; Dou, Yuhai; Ruan, Boyang; Sun, Ziqi; Chou, Shu‐Lei; Dou, Shi Xue
Abstract: Hierarchical SnO2 hollow spheres self‐assembled from nanosheets were prepared with and without carbon coating. The combination of nanosized architecture, hollow structure, and a conductive carbon layer endows the SnO2 ‐based anode with improved specific capacity and cycling stability, making it more promising for use in lithium ion batteries. Abstract : The legend of SnO2 hollow : Combining the advantages of the low‐dimensional nanosized building blocks, hollow structure, and elastic carbon buffering layer, the prepared carbon‐coated hierarchical SnO2 /C hollow spheres show superior reversible capacity, rate stability, and cycle life as an anode for lithium ion batteries.